3D math primer for graphics and game development - Dunn, Fletcher; Parberry, Ian. (Boca Raton, FL : A K Peters/CRC Press, 2011)
'This book presents the essential math needed to describe, simulate, and render a 3D world. It provides an introduction to mathematics for game designers, including fundamentals of coordinate spaces, vectors, and matrices, orientation in three dimensions, introduction to calculus and dynamics, graphics, and parametric curves'--Provided by publisher.
'An A K Peters book.'
Includes bibliographical references (p. 801-805) and index.
Keywords: Computer graphics; Computer games -- Programming; Computer science -- Mathematics